The Relationship between Organizational Silence of Employees and Management style and Professional Ethics of managers - Gholamhassan Panahi; Sajad Kazemi (Allameh Tabataba'i University Press, 2023)
The present study was conducted with the aim of determining the relationship between employees' organizational silence and the management style and professional ethics of managers in Farhangian University of Zahedan. The method of doing descriptive research was correlation. The statistical population includes all employees and managers in Farhangian University of Zahedan city, 130 people, 100 of whom were selected as the sample size through Shadeh random sampling method. The research tools were organizational silence (Vakula and Boradas, 2005), managers' management style questionnaire (Moghimi, 2009) and professional ethics questionnaire (Armito et al., 2011). The content validity of the tool and the reliability of the tool were estimated through Cronbach's alpha coefficient for the organizational silence questionnaire (0.80), managers' management style questionnaire (0.81) and professional ethics questionnaire (0.81). Pearson's correlation coefficient and multivariate regression were used to analyze the research hypotheses. The results of this research showed that there was a significant relationship between organizational silence of employees, management style and professional ethics of managers in Farhangian University. Also, there was a significant relationship between the components of organizational silence of employees with the management style and professional ethics of managers at Farhangian University, and there was also a significant relationship between the management style of managers with the professional ethics of managers and its components at Farhangian University. Among managers' management styles, managers' collaborative management style could predict 68% of employees' organizational silence, and among the components of professional ethics, managers' social responsibility component could predict 60.8% of employees' organizational silence.